Correlation of ki-67 index with volumetric segmentation and its value as a prognostic marker in glioblastoma - Henker, Christian; Kriesen, Thomas; Schneider, Björn; Glass, Änne; Scherer, Moritz; Langner, Sönke; Erbersdobler, Andreas; Piek, Jürgen (World neurosurgery, 2019)
Objective - Previous research has shown a strong correlation between the Ki-67 proliferation index and grade of malignancy in astrocytoma. Ki-67 has also shown encouraging results as a prognostic marker for patients' overall survival (OS). We focus on whether the index is linked to the appearance of glioblastoma on pretreatment magnetic resonance imaging (MRI) or to OS. - Methods - In our retrospective study, only isocitrate dehydrogenase IDH wild-type glioblastoma was included (n = 152). Ki-67 index was quantified via immunohistochemistry. On all pretreatment MRI, tumor compartments (tumor, necrosis, and edema) were volumetrically assessed. An OS subpopulation was filtered from the total cohort (residual tumor volume ≤2 cm3). In addition, a propensity score matching was executed. - Results - All volumetric assessed tumor volumes correlated with each other (P ≤ 0.011), although the Ki-67 index showed no correlation with any of the measured volumes. Concerning the OS, a cutoff value of 20% for the Ki-67 index showed a significant influence on patients' OS in multivariate analysis (P = 0.043). - Conclusions - The unique appearance of every glioblastoma on MRI seems to be independent of the Ki-67 index. Furthermore, the Ki-67 index did show a distinct prognostic value for OS within our cohort at a cutoff value of 20% for Ki-67.